Potential of graphene based photocatalyst for antiviral activity with emphasis on COVID-19: A review. Issue 3 (June 2022) - Patial, Shilpa; Kumar, Abhinandan; Raizada, Pankaj; Le, Quyet Van; Nguyen, Van-Huy; Selvasembian, Rangabhashiyam; Singh, Pardeep; Thakur, Sourbh; Hussain, Chaudhery Mustansar
Abstract: Coronavirus disease-2019 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been one of the most challenging worldwide epidemics of recent times. Semiconducting materials (photocatalysts) could prove effectual solar-light-driven technology on account of variant reactive oxidative species (ROS), including superoxide ( O2 - ) and hydroxyl ( OH) radicals either by degradation of proteins, DNA, RNA, or preventing cell development by terminating cellular membrane. Graphene-based materials have been exquisitely explored for antiviral applications due to their extraordinary physicochemical features including large specific surface area, robust mechanical strength, tunable structural features, and high electrical conductivity. Considering that, the present study highlights a perspective on the potentials of graphene based materials for photocatalytic antiviral activity. The interaction of virus with the surface of graphene based nanomaterials and the consequent physical, as well as ROS induced inactivation process, has been highlighted and discussed. It is highly anticipated that the present review article emphasizing mechanistic antiviral insights could accelerate further research in this field. Graphical Abstract: ga1 Highlights: Potential features of graphene based materials for antiviral activities are highlighted. Perspective of graphene based materials to combat SARS-CoV-2 is presented. Mechanistic insights of photocatalytic viral inactivation are explored. Major challenges involving photocatalytic viral inactivation are mentioned.